The sage of Kanchi - Mahadevan, T. M. P. (Telliyavaram Mahadevan Ponnambalam), 1911-1983 (Sri Kanchi Kamakoti Sankara Mandir, 1983)
Life and mission of Chandrasekharendra Saraswati, Jagatguru Sankaracharya of Kamakoti, b. 1893.